PENGAJARAN â€œENGLISH FOR GUIDINGâ€ BERBASIS PENDEKATAN SOSIOKULTURAL - Astawa, I Nengah (Jurnal Santiaji Pendidikan (JSP), 2011)
Teaching English for specific purposes (ESP), which is in contrast with English for Academic purposes (EAP), has gained specially great attention since 1960’s. One of the examples of ESP is English for guiding. The main purpose of implementing English for tourism in some schools or collages is to give the students ability to communicate mainly orally so as to be able to fulfil the student’s need for his or her future career . In reality very often cultural misunderstandings which may produce fatal consequences emerge among those who are involved in tourism industry. Due to this circumstance, inserting sosio-cultural aspects in the teacher’s language teaching interaction is indeed beneficial. In this case, the role of the teacher to include some cultural aspects in language teaching, beside giving formal grammatical language forms, of course is highly worth considering. Teaching English for tourism industry is not regarded appropriate yet if sosio-cultural aspects are not adequately included. In other words, beside teaching the language forms, English teacher should incorporate sosio-cultural aspects into his/her interaction.